The Israeli Entity’s Challenges Before the International Criminal Court Against the Arrest Warrant for Some Israeli Leaders, Between Rejection and Acceptance - Khadouma, Abdelkader; Fasla, Abdelatif (Journal of Legal Studies and Researches, 2025)
After the issuance of an arrest warrant for some Israeli leaders by the International Criminal Court, Israel has presented and will present other Challenges before this court. This study aims to reveal the extent to which Israel is able to evade the responsibility for its nationals who committed the most serious international crimes in the Gaza Strip, however we believe that it will fail in this regard due to the integrity of the judges of the International Criminal Court.